Innovative utilization of acid mine drainage (AMD): A promising activator for pyrite flotation once depressed in a high alkali solution (HAS)–Gearing towards a cleaner production concept of copper sulfide ore. (15th August 2021) - Bai, Shaojun; Bi, Yunxiao; Li, Jie; Yu, Pan; Ding, Zhan; Lv, Chao; Wen, Shuming
Graphical abstract: Highlights: This study involves a novel way of AMD utilization in the flotation circuit of pyrite. Characteristics of interesting species on samples are determined by ToF–SIMS analysis. The addition AMD increases HAS-depressed pyrite flotation recovery by ∼64% with SIX. Characteristics of interesting species on samples are determined by ToF–SIMS analysis. AMD activation attributes hydrophilic Ca/Fe species removal and Cu sites increase. Abstract: AMD is a major environmental issue during the mine activities of copper sulfide ore. The main objective of the present study is to recover depressed-pyrite from copper sulfide tailings through its activation using AMD. Micro-flotation experiments with high-purity pyrite, Solubility tests and Visual MINTEQ model analysis, X-ray photoelectron spectroscopy analysis (XPS) and Time-of-flight secondary ion mass spectrometry (ToF–SIMS) analysis were conducted. The results indicate that the flotation recovery of HAS (high alkali solution)-depressed-pyrite is increased by~64% with an addition of a volume ratio of AMD to HAS 3:1 and a sodium isoamylxanthate (SIX) dosage of 2.0 × 10 −3 mol/L (6.16 × 10 3 g/t). Solubility tests and Visual MINTEQ model analysis confirm that AMD facilitates the desorptions of calcium ions on the pyrite, forming calcium sulfate specie (CaSO4 ·2H2 O) in the solution. Meanwhile, copper ions can be desirably adsorbed onto the pyrite surface and increase the Cu-active sites. The X-ray photoelectron spectroscopy analysis study confirms that the formation of hydrophilic calcium and iron species is the main reason for the inhibition of pyrite in the HAS system. After the treatment of HAS-depressed-pyrite using AMD, the copper atomic concentration of pyrite is about 1.26% while the CaO/OH content and Fe (III)–OOH content decrease by 26.77% and 27.24%, respectively. ToF-SIMS results further confirm the activation effects of AMD on the HAS-depressed-pyrite. The abundance of Ca +, CaOH +, and FeOH + ion layers on the mineral surface decreases evenly after AMD activation. Additionally, the distribution of C5 H11 + and Cu + ions on the pyrite surface becomes much denser. Consequently, the addition of AMD reinforces the adsorption of dixanthogen and remarkably improves the flotation performance of pyrite. This activation effect is mainly attributed to the combined impacts of the removal of hydrophilic calcium and iron species from the pyrite surfaces and the increase of Cu-active sites on the pyrite surfaces.